2020
DOI: 10.1212/wnl.0000000000010135
|View full text |Cite|
|
Sign up to set email alerts
|

Initial high-efficacy disease-modifying therapy in multiple sclerosis

Abstract: Objective:To determine the effectiveness of high-efficacy disease-modifying therapies (heDMT) versus medium-efficacy disease-modifying therapies (meDMT) as the first treatment choice in treatment-naïve patients with multiple sclerosis (MS) on disability worsening and relapses. We assessed this using a nationwide population-based MS registry.Methods:We identified all patients starting a heDMT as first-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
90
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 36 publications
8
90
1
2
Order By: Relevance
“…Four recent real-world retrospective studies compared the ESC and the EIT strategies, suggesting an association of the latter strategy with a lower hazard of clinical relapses, a lower mean change in EDSS score at 5 years, a higher median time to sustained accumulation of disability and a lower risk of conversion to secondary progressive MS (SPMS), compared with initial treatment with first-line agents. 12 , 13 , 22 , 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four recent real-world retrospective studies compared the ESC and the EIT strategies, suggesting an association of the latter strategy with a lower hazard of clinical relapses, a lower mean change in EDSS score at 5 years, a higher median time to sustained accumulation of disability and a lower risk of conversion to secondary progressive MS (SPMS), compared with initial treatment with first-line agents. 12 , 13 , 22 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, a Danish observational study proved a lower probability of a 6-month confirmed EDSS score worsening and of a first relapse over a follow-up of 4 years for 194 patients starting their therapy with high-efficacy DMTs compared with 194 PS matched patients starting with medium-efficacy DMTs. 27 …”
Section: Discussionmentioning
confidence: 99%
“…The current disease modifying therapies (DMTs) effectively inhibit formation of focal lesions (Buron et al, 2020), but their effect on non-lesional inflammatory activities is unknown. Understanding contributions of lesional versus non-lesional MS inflammatory activity to CNS tissue destruction requires reliable and simultaneous measurements of both processes in the same patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the optimal treatment strategy with DMTs in RRMS remains elusive [2,[7][8][9]. Current treatment approaches may miss a window of opportunity for achieving the highest effectiveness of DMTs [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%